Managerial Finance / Ninth Edition - Copeland Thomas E; Fred Weston J (The Dryden Press, 1992)
Fundamental Concepts of Managerial Finance, The Nature of Finance, Decisions Across Time, The Environment for Financial Decisions, Business Organization and Taxes, Depreciation Methods, Basic Financial Planning and Investment, Financial Analysis, The Normal Distribution, Decision Making under Uncertainty, Risk and Return: Theory, Options on Risky Assets, Managing Financial Risk, Risk and Valuation, Financial Structure and the Cost of Capital, The State-Preference Model, Dividend Policy, Financial Strategies for Working Management, Short-Term Financial Management, The Treasurer's Long-Range Financial Strategies, Common Stock Financing, Lease Financing, Warrants and Convertibles, Dynamic Strategies for Increasing Value, Financial Distress, Appendices, Author and Subject Index.
Fundamental Concepts of Managerial Finance, The Nature of Finance, Decisions Across Time, The Environment for Financial Decisions, Business Organization and Taxes, Depreciation Methods, Basic Financial Planning and Investment, Financial Analysis, The Normal Distribution, Decision Making under Uncertainty, Risk and Return: Theory, Options on Risky Assets, Managing Financial Risk, Risk and Valuation, Financial Structure and the Cost of Capital, The State-Preference Model, Dividend Policy, Financial Strategies for Working Management, Short-Term Financial Management, The Treasurer's Long-Range Financial Strategies, Common Stock Financing, Lease Financing, Warrants and Convertibles, Dynamic Strategies for Increasing Value, Financial Distress, Appendices, Author and Subject Index.